Location Analysis of The Best Climate Village in Paser Regency Using Technique for Order Preference by Similarity to Ideal Situation (TOPSIS) - Syafruddin Anshari; Sri Listyarini; Subekti Nurmawati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2023)
Since the enactment of the National Registration System (SRN) of the Directorate General of Climate Change Control based on the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number 71 of 2017 where SRN is a forum to manage and provide web-based data and information in the form of actions and resources in the implementation of climate change adaptation and mitigation actions in Indonesia. Until 2023, there are 16 climate village locations in Paser Regency that have been reported to SRN with various levels of achievement according to the conditions of action that have been carried out by each climate village location. The purpose of this study is to analyze the best location of climate villages as reference locations in efforts to adapt and mitigate climate change in Paser Regency. The method used is TOPSIS, which calculates the highest value to the lowest of the closing results. From the results of the analysis, it was found that the best location of the climate village in Paser Regency that can be recommended as a reference location for ProKlim development is Muser Village, Muara Samu District, Paser Regency.